Gender gap in study inclusion: Insights from the STAR-FIB cohort study. (19th May 2022) - Tanner, H; Goulouti, E; Lam, A; Elchinova, E; Nozica, N; Servatius, H; Noti, F; Seiler, J; Baldinger, SH; Haeberlin, A; Franzeck, F; Asatryan, B; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Swiss National Science Foundation Swiss Heart Foundation Background: The underrepresentation of women in cardiovascular clinical trials is well described but cannot be fully explained by sex-specific differences in the prevalence of cardiovascular diseases. Data on potential sex- and gender-related differences in study exclusion reasons are scarce. The STAR-FIB cohort study aimed to estimate the age and sex-specific prevalence of screening-detected atrial fibrillation (AF) in 800 hospitalized patients aged 65-84 years using serial seven-day ECGs. Recruitment for study inclusion was stratified by sex (female/male, as stated in the patient's records) and age (four age bands, ≥65 to <70, ≥70 to <75, ≥75 to <80, and ≥80 to <85 years), and was truncated for each subgroup after the inclusion of 100 participants. Purpose: To assess sex and gender differences in patient recruitment for inclusion in the STAR-FIB cohort study. Methods: A screening log containing sex-category, age, and reasons for exclusion was maintained. Exclusion criteria are shown in the figure. For the purpose of the present study, an explorative analysis of all exclusion criteria with respect to sex category was done. Results: Overall, 11'470 patients were identified for eligibility, 795 patients (49% women; mean age 75 years) were enrolled, and 10'675 patients (52% women vs. 48% men, p =0.13) were not enrolled. The two major exclusion reasons were unwillingness to participate, which was more frequent in women (27.9% of women vs. 18.4% of men, p < 0.01), and the presence of clinical AF, which was more prevalent in men (27.1% of men vs. 20.5 % of women, p < 0.01). A detailed analysis of all exclusion criteria analysed by sex category is provided in the figure. Conclusions: Clinical AF was more frequent in men, in accordance with the well described sex-driven (biological) higher prevalence of AF in men. In contrast, we found a higher percentage of women unwilling to participate in this study, which may represent a more gender-based (sociocultural) phenomenon. A further exploration of these findings should be performed and may help to identify and potentially overcome modifiable obstacles for study participation.